NEGOTIATING TRADITION AND MODERNITY: THE DIALECTICS OF CONSERVATISM AND PROGRESSIVISM IN TEMBANG SUNDA CIANJURAN - Budiman, Arif (Universitas Gadjah Mada, 2025)
Innovation in traditional arts often triggers polemics between conservative and progressive values. This study offers a dialectical model of innovation-response in traditional arts by using Tembang Sunda Cianjuran as a case study to integrate Lewis A. Coser’s functional conflict theory. Employing a qualitative methodology that combines case study and autoethnography, data were gathered through in-depth interviews, participant observation, and documentary analysis. This multi-method approach allowed for a comprehensive understanding of both the artistic negotiation process and the underlying community dynamics. The research found that (1) the innovation of